Changes in the temperature distribution in the top 150 m of the equatorial Indian Ocean in association with El Niño and monsoon drought. (4th September 2018) - Roose, Shinto; Joseph, Porathur V.; Mohanakumar, K.
Abstract : The vertical temperature profiles of the equatorial Indian Ocean between the latitudes 5°S and 5°N in years of El Niño and monsoon drought have been studied using quality controlled ocean temperature (EN4) data set of the UK Met Office Hadley Centre and Simple Ocean Data Assimilation (SODA) reanalysis data. The temperature anomalies in the equatorial Indian Ocean were studied in three composites: (a) years of El Niño with no drought monsoon (composite A), (b) years of El Niño associated with drought monsoon (composite B) and (c) years of monsoon drought without El Niño (composite C). In composite A, a prominent subsurface dipole (SSD) in temperature is seen between depths of 60 and 120 m during the months September–November. It is not present in composite B. SSD is associated with surface wind anomalies, easterly in the equatorial central Indian Ocean and southeasterly in the equatorial eastern Indian Ocean. Drought monsoons have strong westerly surface wind anomalies in the equatorial central Indian Ocean, which reduces the strength of the equatorial easterly wind anomaly in composite B. In composite C, a negative SSD developed due to the strong anomalous westerly wind over the equatorial Indian Ocean associated with monsoon drought and the absence of El Niño induced equatorial easterly winds. Abstract : Zonal surface wind values over the box (60°–110°E, 10°S–5°N) for the period 1979–2001 using ERA40 (black line) and ERA‐Interim (red line).